Albania : Poverty Assessment - World Bank; World Bank (Washington, DC, 2013)
Despite the impressive performance of the economy in the last five years, however, poverty in Albania has remained high, and per capita income, at around US$1,230 in 2002, has remained one of the lowest among transition economies. In an effort to adopt policies to share widely the benefits of growth, and reduce poverty, the Government outlined a poverty alleviation strategy in the 2000 Interim Poverty Reduction Strategy Paper (I-PRSP), and developed it in detail two years later in the Growth and Poverty Reduction Strategy (GPRS), the precursor to the current National Strategy for Socio-Economic Development (NSSED). However, in recognition of the data limitations, the first round of a five-year Living Standards Measurement Survey (LSMS) program was launched in 2002. This survey provides valuable information on a variety of issues related to living conditions in Albania, including details on income and non-income dimensions of poverty in the country, and, forms the basis of the present assessment of poverty in Albania. The poverty line used for this assessment is the first absolute poverty line based on nationally representative, household level expenditure data ever estimated for Albania, and is based on an actual consumption data. Poverty in Albania has marked spatial and regional dimensions, with rural areas and the Mountain region being consistently poorer than rest of the country, stipulating the depth of poverty in the Mountain area is much more pronounced than in any other region, with a poverty gap index of over 11 percent. The study reviews the determinants of poverty, through the main characteristics of poor households, and labor market characteristics of the poor, noting widespread unemployment rate in urban areas. It then examines the non-income dimensions of poverty, health and education inequalities, and reviews the role of social transfers, determining pensions - and remittances from Albanian relatives - are the largest sources of transfer income. The results of the analysis point priority areas, namely, that coverage under health insurance needs to be increased; secondary school enrollments need to be increased, and quality of education at this level improved; provision of basic services and infrastructure should be improved, including access to quality health and education services and to basic sanitation services; and, it is imperative that the Government develops a rural development strategy focused on poverty reduction in the short run, since a large number of the poor live in rural areas. Agriculture is the key income generating activity in these areas, thus locally adapted rural extension service should be provided. In terms of future growth, attention must necessarily shift to the manufacturing sector, for stimulating the manufacturing sector could potentially create increased employment opportunities, while another area that deserves great attention is tourism.